ANALYTICAL HIERARCHY PROCESS APPROACH ON CONSUMER PREFERENCE IN BEER BRAND SELECTION. CASE STUDY: BIR BINTANG, ANKER, BALIHAI - Bolung, Clairy .; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: This research is will be conducted in Manado city. 2017. Population in this research is people in Manado who has drink and have experience with Bir Bintang, Bali Hai and Anker. The sample of this research is all consumer of Bir Bintang, Bali Hai, Anker for about 50 respondents that who has drink and have experience with Bir Bintang, Bali Hai and Anker. Consumer preference is measured in terms of the level of satisfaction from consuming various of beer brand. Beer brand criteria means factors of the beer brand are Price, Taste, Packaging, Advertisement, Peer Influence. Based on the result and discussion, two conclusions can be formulated, Price is the criteria that influence the most in selecting a beer brand, followed consecutively by taste, peer influence, packaging and advertisement. Bir Bintang is the most chosen beer brand in Manado, Bir Bintang became the most preferred beer brand because it excels in four criteria; taste, advertising, packaging, and peer influence, and in the second position is Anker, and Bali Hai in the last position. Bali Hai should improve the quality in terms of taste, because the cheaper price is not necessarily will be selected by consumersKeywords: consumer preference, brand selection, beer brand, criteria most influence.